2019
DOI: 10.1073/pnas.1905172116
|View full text |Cite
|
Sign up to set email alerts
|

HuR counteracts miR-330 to promote STAT3 translation during inflammation-induced muscle wasting

Abstract: Debilitating cancer-induced muscle wasting, a syndrome known as cachexia, is lethal. Here we report a posttranscriptional pathway involving the RNA-binding protein HuR as a key player in the onset of this syndrome. Under these conditions, HuR switches its function from a promoter of muscle fiber formation to become an inducer of muscle loss. HuR binds to the STAT3 (signal transducer and activator of transcription 3) mRNA, which encodes one of the main effectors of this condition, promoting its expression both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Recent evidence reveals several scenarios of miRNAs accumulating in hepatocytes by NAFLD dysregulation. miRNAs have been shown to possess the ability to directly bind proteins [ 29 ] and induce gene expression as well [ 30 ]. miRNAs are known to have a direct impact on the expression of PPARγ, which mediates expression of many downstream genes [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence reveals several scenarios of miRNAs accumulating in hepatocytes by NAFLD dysregulation. miRNAs have been shown to possess the ability to directly bind proteins [ 29 ] and induce gene expression as well [ 30 ]. miRNAs are known to have a direct impact on the expression of PPARγ, which mediates expression of many downstream genes [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, HuR associates with lncRNA SPRY4-IT1 to synergistically increase the stability and translation of mRNAs encoding tight-junction proteins (23), and it also directly interacts with lncRNA H19 to prevent the processing of miRNA 675 (miR-675) from H19 (24). HuR competes with miR-195 to modulate Stim1 mRNA stability antagonistically (25) and also counteracts miR-330 to promote STAT3 translation (26). Targeted deletion of HuR in IECs inhibits regeneration of the intestinal mucosa (27), reduces tumor development (18), delays repair of damaged mucosa induced by mesenteric ischemia/reperfusion in the small intestine and by dextran sulfate sodium in the colon (28), impairs Paneth cell function (15), and alters Rac1 nucleocytoplasmic shuttling in the intestinal epithelium (29).…”
mentioning
confidence: 99%
“…However, the regulation of HuR in inflammation is controversial. Mubaid et al (2019) found that HuR overexpression promotes the inflammation by promoting the translation of STAT3 in muscular dystrophy, and Krishnamurthy et al (2010) found that HuR knockdown can attenuate the inflammatory response after myocardial infarction in IL-10deficient mice, by reducing the mRNA expression of TNF-α and TGF-β; however, Yiakouvaki et al (2012) found that high expression of HuR can protect mice from inflammation in pathological enteritis; Ceolotto et al (2014) found that HuR suppresses chronic inflammation, associated with endothelial injury, by stabilizing the mRNA of SIRT1. In the current study, we found that HuR is negatively related to inflammation in IVDD, because the expression of IL-6, IL-1β, TNF-α, and iNOS was higher in HuR knockdown and the TNF-α-treated group than in the TNF-α-alone group.…”
Section: Discussionmentioning
confidence: 99%